(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent decades, a steady increase in allergic diseases has been recorded. In the structure of childhood pathology, bronchial asthma (BA) and allergic rhinitis (AR) occupy one of the leading places in terms of prevalence. The prevalence of BL among children and adolescents ranges from 3% to 15% and significantly exceeds official statistics. The share of AR in the overall structure of allergic diseases is extremely high (60-70%). The prevalence of AR is especially high in the child population, where it reaches 10 - 28.7%. In children suffering from AR in combination with BA - hypertrophy and chronic inflammation of the pharyngeal tonsil (PM), is the most common pathology of the ENT organs and, according to various authors, ranges from 30 to 86%. It has been proven that ENT diseases can be the cause or aggravating background of the course of BA, reduce the effectiveness of the therapy and worsen the prognosis of the disease. In connection with the emergence of the theory of lymphogenesis, a tendency is developing towards a more gentle, conservative method of treating hypertrophy and inflammation of the brain. Most clinicians believe that any surgical intervention on the upper respiratory tract (URT1), performed without taking into account the state of the body’s reactivity, can become a powerful provoking factor in the aggravation of allergies in other organs and systems, and also cause a severe exacerbation of the disease. However, despite significant advances in the treatment of these diseases, the possibilities of therapeutic regimens for a combination of AR with pathology of the lymphopharyngeal ring (LPR) remain limited. The lack of effect from the therapy for chronic pathology of the brain in children with AR and BA affects the quality of life (QOL) of these children. All this forces us to expand the search for conservative treatment methods and resort to surgical treatment. In recent years, isolated works of foreign and domestic researchers have appeared, indicating a favorable effect of adsnotomnes on allergic diseases of the respiratory tract. However, to date there is no single point of view on the treatment of children with chronic adrenalitis, hypertrophy of the GM and AR in combination with bronchial asthma, and discussions on this topic continue.